Analysis of Risk Management in the Ka'fa Adam Seed Business in North Payakumbuh Tarok in the Perspective of Sharia Business - Hidayatul Sofianis; Habibatur Ridhah (Universitas Mercu Buana, 2023)
The purpose of this study is to find out how the analysis of risk management in the Ka'fa Adam seed business is carried out from a sharia perspective and how the risk is managed and mitigated by the owner. The research method is qualitative where the researcher collects evidence-based research data in the field and interviews with the main source of information, namely the owner of the Bibit Ka'fa Adam shop. The results of this study indicate that the implementation of risk management in the operations of Ka'fa Adam Bibit has been carried out properly, namely through the application of appropriate management processes and functions. The risk management carried out is to identify and understand the risks that arise in this company, the owner finds many emerging risks that need to be addressed immediately so that large losses do not occur. The risk analysis carried out is to determine the possibility and consequences of the risks that may arise, the owner must know the possible risks that may arise. The risk assessment carried out is to compare the level of each risk and identify the type that occurs most often, namely the risk of unstable sales due to business competition, full storage and one way seeding. Orders canceled by consumers. Risk management is carried out, namely the owner tries to minimize and overcome it well, he adopts some Islamic values, but not all of them. It is done according to Islam which talks about honesty and fairness.